2012
DOI: 10.1021/om300815b
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Conjugated Homo- and Heterobichromophoric Complexes of Tetracene and Pentacene

Abstract: Homobichromophoric platinum(II) complexes containing tetracenyl rings (T-Pt-T) and pentacenyl rings (P-Pt-P) were synthesized by Sonogashira coupling between trans-[Pt(PEt 3 ) 2 I 2 ] and 5-ethynyl-12-[(triisopropylsilyl)ethynyl]tetracene (T-SiH) and 6-ethynyl-13-[(triisopropylsilyl)ethynyl]pentacene (P-SiH), respectively. A heterobichromophoric complex consisting of tetracenyl and pentacenyl rings (T-Pt-P) was generated by coupling P-SiH and platinated T-SiH. The homobichromophoric complexes were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 78 publications
2
25
0
Order By: Relevance
“…The synthesis of Pt-acetylide complexes is well-documented in the literature. [41][42][43][44] They are typically formed via the reaction of a terminal acetylene with cis-or trans-PtCl 2 (R 3 P) 2 , giving the thermodynamically more stable trans-isomer in both cases when the reaction is conducted at room temperature. Thus, terminal acetylene 1 (ref.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of Pt-acetylide complexes is well-documented in the literature. [41][42][43][44] They are typically formed via the reaction of a terminal acetylene with cis-or trans-PtCl 2 (R 3 P) 2 , giving the thermodynamically more stable trans-isomer in both cases when the reaction is conducted at room temperature. Thus, terminal acetylene 1 (ref.…”
Section: Synthesismentioning
confidence: 99%
“…This nding is in sound agreement with the absorption spectra reported by Nguyen and Yip. 41 Upon cooling to 85 K, an overall sharpening of the absorption features allows for determining the precise position of the maxima in PrCN: 510, 553, 604, 652 and 709 nm for mono-Pt; 510, 555, 608, 658 and 715 nm for trans-Pt; and 510, 553, 592, 640 and 694 nm for cis-Pt. Of particular interest is the 709 nm maximum for mono-Pt, which red-shis to 715 nm in the case of trans-Pt and blue-shis to 694 nm in the case of cis-Pt.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Much less attention has been placed on incorporation of transition metals as a component of the molecular spacer in order to dissect the role of the heavy atom effect in SF. [40] Recently, we reported on a set of transand cis-platinum bridged pentacene dimers. We demonstrated that the presence of platinum does not perturb the 1 (T 1 T 1 ) generation.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational structuring is a characteristic asset of a 3 IL-based emission arising from a ligand-centered excited state where the heavy metal atom has only small contributions but efficiently triggers the otherwise forbidden S1→T1 intersystem crossing (ISC) of a coordinated ligand owing to its large spin-orbit coupling constant [19]. Typical examples of such behavior are Pt alkynyl complexes [57][58][59][60][61][62][63][64][65][66][67]. The latter notion is further supported by the computed spin density surface for the T1 state of complex 2 as it is depicted in Figure 10a.…”
Section: Absorption and Emission Propertiesmentioning
confidence: 99%